Early antibiotic use and incidence of necrotising enterocolitis in very preterm infants: a protocol for a UK based observational study using routinely recorded data. Issue 11 (15th November 2022) - Shen, Rene; Embleton, Nicholas; Lyng Forman, Julie; Gale, Chris; Griesen, Gorm; Sangild, Per Torp; Uthaya, Sabita; Berrington, Janet
Abstract : Introduction: Necrotising enterocolitis (NEC) remains a major contributor to preterm mortality and morbidity. Prolonged duration of antibiotic therapy after delivery is associated with later NEC development but recent evidence suggests that absence of antibiotic treatment after delivery may also increase NEC risk. We will explore this controversy using a large pre-existing dataset of preterm infants in the UK. Methods and analysis: This is a retrospective cohort study using data from UK National Neonatal Research Database (NNRD) for infants born 1 January 2012 to 31 December 2020. Eligible infants will be <32 weeks gestation, alive on day 3. Primary outcome is development of severe NEC, compared in infants receiving early antibiotics (days 1–2 after birth) and those not. Subgroup analysis on duration of early antibiotic exposure will also occur. Secondary outcomes are: late onset sepsis, total antibiotic use, predischarge mortality, retinopathy of prematurity, intraventricular haemorrhage, bronchopulmonary dysplasia, focal intestinal perforation and any abdominal surgery. To address competing risks, incidence of death before day 7, 14 and 28 will be analysed. We will perform logistic regression and propensity score matched analyses. Statistical analyses will be guided by NEC risk factors, exposures and outcome presented in a causal diagram. These covariates include but are not limited to gestational age, birth weight, small for gestational age, sex, ethnicity, delivery mode, delivery without labour, Apgar score, early feeding and probiotic use. Sensitivity analyses of alternate NEC definitions, specific antibiotics and time of initiation will occur. Ethics and dissemination: We will use deidentified data from NNRD, which holds permissions for the original data, from which parents can opt out and seek study-specific research ethics approval. The results will help to determine optimal use of early antibiotics for very preterm infants. Implications: This data will help optimise early antibiotic use in preterm infants. Trial registration number: ISRCTN55101779 .